2008
DOI: 10.1007/s11120-008-9378-y
|View full text |Cite
|
Sign up to set email alerts
|

The D1 and D2 proteins of dinoflagellates: unusually accumulated mutations which influence on PSII photoreaction

Abstract: Plastid encoded genes of the dinoflagellates are rapidly evolving and most divergent. The importance of unusually accumulated mutations on structure of PSII core protein and photosynthetic function was examined in the dinoflagellates, Symbiodinium sp. and Alexandrium tamarense. Full-length cDNA sequences of psbA (D1 protein) and psbD (D2 protein) were obtained and compared with the other oxygen-evolving photoautotrophs. Twenty-three amino acid positions (7%) for the D1 protein and 34 positions (10%) for the D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Understanding of the photosynthetic machinery gene homologs and their organization has recently advanced with sequencing of the Symbiodinium chloroplast and nuclear genomes ( Shoguchi et al, 2013 ; Barbrook et al, 2014 ; Mungpakdee et al, 2014 ). Previously, characterization of Symbiodinium photosystem subunit proteins and genes has examined PS II core proteins psbA (D1 protein) and psbD (D2 protein), PS II manganese-stabilizing protein (or PsbO protein) encoded by psbO , and PS I core protein psaA (P 700 protein; Iglesias-Prieto and Trench, 1997 ; Warner et al, 1999 ; Iida et al, 2008 ; Takahashi et al, 2008 ; McGinley et al, 2012 ; Castillo-Medina et al, 2013 ; Gierz et al, 2016 ). Photoinhibition of PS II and decreased expression of PS II D1 protein (D1 protein content and psbA gene expression) have been observed in thermally stressed Symbiodinium cells ( Takahashi et al, 2008 ; McGinley et al, 2012 ; Gierz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of the photosynthetic machinery gene homologs and their organization has recently advanced with sequencing of the Symbiodinium chloroplast and nuclear genomes ( Shoguchi et al, 2013 ; Barbrook et al, 2014 ; Mungpakdee et al, 2014 ). Previously, characterization of Symbiodinium photosystem subunit proteins and genes has examined PS II core proteins psbA (D1 protein) and psbD (D2 protein), PS II manganese-stabilizing protein (or PsbO protein) encoded by psbO , and PS I core protein psaA (P 700 protein; Iglesias-Prieto and Trench, 1997 ; Warner et al, 1999 ; Iida et al, 2008 ; Takahashi et al, 2008 ; McGinley et al, 2012 ; Castillo-Medina et al, 2013 ; Gierz et al, 2016 ). Photoinhibition of PS II and decreased expression of PS II D1 protein (D1 protein content and psbA gene expression) have been observed in thermally stressed Symbiodinium cells ( Takahashi et al, 2008 ; McGinley et al, 2012 ; Gierz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Species of Symbiodiniaceae have been previously shown to be differentiated by mutations on genes related to photosystem machinery. Wham, Ning & LaJeunesse (2017) found that Durusdinium glynnii was distinguished from other symbionts within the genus Durusdinium as well as from symbionts of other genera by a non-synonymous mutation that effected a change on the D1 protein of photosystem II (psbA gene), a highly conserved region in dinoflagellates (Iida et al, 2008). This could indicate that differences in temperature and/or light environment between VA and RI are driving adaptive differentiation of B. psygmophilum populations at loci related to photosynthetic machinery.…”
Section: Outlier Snps Related To Coral Stress Response and Energeticsmentioning
confidence: 99%
“…The PS II protein complex contains the inner antenna protein CP, as well as two core polypeptides, D1 and D2, which are all essential components of the PS II complex [ 32 ]. P680, Pheophyll (Pheo), and special plastoquinone (QA and QB) are combined on D1 and D2 [ 36 ]. The outer layer of PS II is the PS II concentrated light-harvesting pigment complex (LHCII), which is composed of a photosynthetic pigment and a protein [ 37 ].…”
Section: Discussionmentioning
confidence: 99%